Evaluation of efficacy of curcumin along with lycopene and piperine in the management of oral submucous fibrosis - Basudev Mahato; Chandraday Prodhan; Samir Mandal; Avirup Dutta; Parna Kumar; Tushar Deb; Tarun Jha; Keya Chaudhuri (Wolters Kluwer Medknow Publications, 2019)
Context: Oral submucous fibrosis (OSMF) is a high-risk premalignant condition of the oral cavity and oropharynx. Complete regression of the disease is still not possible with available treatment modalities. Aims: The aim of the study was to evaluate the efficacy of curcumin, lycopene, and piperine as a combination in the management of OSMF. Settings and Design: Efficacy was evaluated on the basis of improvement in clinical parameters (i.e., visual Analog Scale [VAS]) score for burning sensation, mouth opening (MO), mucosal flexibility (MF), and tongue protrusion [TP]). Materials and Methods: Forty patients clinically and histopathologically diagnosed with OSMF were included in the study; patients were administered with the above-stated drug combination, and clinical parameters were evaluated at regular intervals to compare the pre- and post-treatment measurements. Statistical Analysis Used: Paired t-test was done to evaluate significance of the results. Results: Highly significant improvement was observed for posttreatment reduction in VAS score for burning sensation and increase in MO (P < 0.001). Significant improvement was also observed in the increase of MF and TP. Posttreatment histopathological evaluation also revealed reepithelialization, indicated by significant increase in the epithelial thickness as found through quantitative image analysis. Immunohistochemical studies with Col1A1 showed decrease in collagen deposition. Conclusions: Taken together, the present study proposes the usage of combination drug therapy for the management of OSMF as an effective and affordable way.